NATURE OF EMOTIONS IN ANAMIKA'S POETRY - Yadav, Preeti; Meena, Dhanesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Emotions are directly related to consciousness which connects the poet to this world and maintains the specialty of both. In literature, the element of emotions is expressed through words. The poet takes the help of expression skills for this expression. Thus, it can be said that the poet is an expert in the expression of poetic emotions whose basis of poetic emotions is the social environment of the time, by experiencing which he expresses himself and others. In giving form and direction to Anamika's poetic emotions, the natural beauty of Bihar, human happiness and sorrow, life view influenced by Tolstoy's spirit of public welfare, life-force relation, etc. The theory has directly or indirectly influenced feminist consciousness. The effect of any object, emotion or situation on the heart and the reaction to it is called empathy. This can also be understood in another way. This world is so big and full. It has so many colors and forms. There are so many substances, so many objects. Every object, every event affects us in some way or the other. Just like throwing a pebble in water creates waves, similarly when we see or hear something or when something happens to us, we also react. Our heart is affected and then a feeling is generated according to this effect. This effect of objects on the heart and the reaction generated from it is called empathy. While talking about different forms of empathy, the first thing that we should always keep in mind is that nothing can happen in the air. । Meaning to say is that when we are talking about a poet, his poetry has to be kept in front. । Every word of the poem has to be read and understood. । Anamika is from Bihar state, so the effect of Bihar state can be seen on her poetry. । One's personal experience or knowledge towards others through one's senses is called sympathy. । According to Hindi Gyan Kosh, sympathy means- The understanding or experience or feeling that happens in the mind. । The sorrow or sympathy that arises in the mind after seeing someone's grief, sorrow, loss, suffering etc. is called sympathy. । Pain arising from the pain of others. । Sympathy means experience or knowledge gained through the senses, but nowadays it is generally used more in the sense of sympathy. । In psychology, this word is still used in its original meaning and in that sense it is the first conscious reaction of the body part towards any external stimulus. । In return for this, the person gets knowledge about his surroundings. । For sympathy, any The presence of a stimulant is considered essential; only the qualities related to it arouse sensitivity in humans.